CONTROLLING Aedes aegypti POPULATION AS DHF VECTOR WITH RADIATION BASEDSTERILE INSECT TECHNIQUE IN BANJARNEGARA REGENCY, CENTRAL JAVA - Siti Nurhayati; Bambang Yunianto; Tri Ramadhani; Bina Ikawati; Budi Santoso; Ali Rahayu (BATAN, 2013)
The control program of dengue hemorrhagic fever (DHF) in Indonesia is still a problem due tothe incomplete integrated handling. Sterile insect technique (SIT) for Aedes aegypti as DHFvector was considered as a potential strategy for controling the DHF. A preliminary survey wascarried out to to determine the characteristic of A. aegypti population in the study site before theimplementation of SIT. The implementation of radiation based-SIT was carried out in Krandeganand Kutabanjar Villages of Banjarnegara Regency, Central Java which involved 99 houses. Onehundred gamma rays irradiated male mosquitoes were released to each house up to five times.The eggs, larvae and adult mosquitoes were collected using ovitrap and weekly observed. Theinitial population density of A. aegipty in the studied area was obtained to be 6 mosquitoes perhouse with the mean index of house was 15.86 % and the mean sterility of sterilizedmosquitoes was 79.16 %. The SIT effectively reduced A. aegipty population after the fifthrelease of irradiated mosquitoes into the houses. It can be assumed that the SIT was effectivein controlling DHF vector in the studied area, nevertheles, it will be more effective if it iscombined with other handling techniques.